Analyzing the external determinants and their impact on the market value of banks and industrial sector companies - Salaheldeen Moammed AL- Emam; Tahseen Assi Jassim al-Hmailah (Journal of Madenat Alelem University College, 2022)
This study aimed to identify the main determinants of the performance of the Iraq Stock Exchange. A set of macroeconomic variables (foreign exchange rates, GDP, and crude oil prices) are studied, and their role in explaining the fluctuations in the market value of ordinary shares of companies listed on the Iraq Stock Exchange, and the study is based on a main hypothesis: “The value of ordinary shares is expected to respond. The determinants surrounding the Iraqi market for securities. "The study found a number of results, the most important of which are: The rise in crude oil prices and the increase in the value of the gross domestic product lead to an increase in the market value of the shares of some companies listed on the Iraq Stock Exchange. While the exchange rate has no effect on the market value of the shares of companies listed in the Iraqi market stock.